Strelitziana sarbhoyi sp. nov. (Strelitzianaceae, Chaetothyriales), from North-Western Himalayas, India, described based on morphology and molecular phylogeny - Rana, Shiwali; Singh, Sanjay Kumar; Singh, Paras Nath (Phytotaxa, 2019)
Strelitziana sarbhoyi is established as a new species to accommodate a phylloplane fungus isolated from Mallotus philippensis collected from Kangra region of North-Western Himalayas, Himachal Pradesh. The identity of the fungus is confirmed based on the asexual-morphs, cultural characteristics and phylogenetic analyses of the internal transcribed spacer (ITS) rDNA and partial nuclear ribosomal 28S large subunit (LSU) sequence data. The placement of S. sarbhoyi in the phylogenetic tree was determined based on DNA sequences from authenticated isolates of Strelitziana. Strelitziana sarbhoyi shows nearly 94% similarity with other known species of Strelitziana. Area description is provided for the proposed taxon along with microscopic images, and a phylogenetic tree. This is probably the first report of Strelitziana from India. Holotype specimen (dried voucher culture) is deposited in the Ajrekar Mycological Herbarium (AMH), and an ex-type culture is deposited in National Fungal Culture Collection of India (NFCCI).